Body, education and school discipline in Cuba:control devices from the hygienists speeches (1899-1958) (Tzintzun, Revista de Estudios Históricos, 2016)
This article seeks to establish the contributions of hygienistsspeeches to treat behaviors among school years between the formalizationof the first U.S. military occupation, on January 1, 1899,and the triumph of the Cuban revolution in 1959. The structure assumedmeets the definition context of three moments in the pedagogicaltreatment of school behavior from the references providedby hygienist science in different types: physical hygiene, physiologicalhygiene and mental hygiene.
Keywords: hygiene; discipline; school behavior; Cuba